2017
DOI: 10.1002/ecs2.1740
|View full text |Cite
|
Sign up to set email alerts
|

Extreme drought, host density, sex, and bullfrogs influence fungal pathogen infection in a declining lotic amphibian

Abstract: Briggs. 2017. Extreme drought, host density, sex, and bullfrogs influence fungal pathogen infection in a declining lotic amphibian. Ecosphere 8(3):e01740. 10. 1002/ecs2.1740 Abstract. Freshwater biodiversity is imperiled across the globe, and multiple stressors such as habitat alteration, non-native species invasion, disease, and climate change can act in concert to threaten vulnerable taxa. The amphibian chytrid fungus Batrachochytrium dendrobatidis (Bd), which causes the disease chytridiomycosis, is one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 101 publications
(126 reference statements)
5
63
0
Order By: Relevance
“…While some laboratory studies have suggested that bullfrogs may not always make suitable reservoir hosts for Bd (Eskew, Worth, Foley, & Todd, ; Gervasi et al., ), our observation that bullfrogs have the highest Bd prevalence and loads among species sampled in the field (Figure ), and previous work showing that bullfrog sympatry is an important predictor of Bd infection in R . boylii (Adams et al., ), supports the hypothesis that bullfrogs are a vector of Bd in California, including where R . boylii are extant.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…While some laboratory studies have suggested that bullfrogs may not always make suitable reservoir hosts for Bd (Eskew, Worth, Foley, & Todd, ; Gervasi et al., ), our observation that bullfrogs have the highest Bd prevalence and loads among species sampled in the field (Figure ), and previous work showing that bullfrog sympatry is an important predictor of Bd infection in R . boylii (Adams et al., ), supports the hypothesis that bullfrogs are a vector of Bd in California, including where R . boylii are extant.…”
Section: Discussionmentioning
confidence: 53%
“…Although the interviews and histological examinations presented here, combined with a field study (Adams et al., ), indicate that R . boylii populations in central and northern California have also been affected by Bd and flooding, differences in environmental context may have contributed to a different outcome.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations